Increase in efficiency of electric powered diamond grinding of conductive material by regulating longitudinal profile of grinding wheels - Dobroskok, Vladimir; Shpilka, Andrei; Morneva, Marina; Shpilka, Nikolai (Polska Akademia Nauk Oddział w Lublinie, 2014)
The method of increasing the efficiency of electric powered diamond grinding of hard-tomachine materials which provides the reduction of vibration by forming rational longitudinal profile of working wheel’s surface is presented. The prerequisites and peculiarities of vibration absorbing, technological equipment for implementing the suggested method are described.

Представлен метод повышения эффективности процесса электроалмазного шлифования труднообрабатываемых материалов, обеспечивающий снижение вибраций путем формирования на круге рационального продольного профиля рабочей поверхности. Рассмотрены предпосылки и особенности гашения вибраций, технологическое оборудование для реализации предлагаемого метода.
Повышение эффективности процесса электроалмазного шлифования токопроводящих материалов путем регулирования продольного профиля кругов
Keywords: electric powered diamond grinding; wheel’s working surface; longitudinal profile; vibration absorbing; шлифование электроалмазное; поверхность рабочая; профиль продольный; снижение вибраций